Proposed Digital Marketing Strategy To Increase Brand Awareness In Advertising Industry (Case Study: PT Saji Media Pratama) - Muhammad Farell Javier; Yuanita Handayati; Asnan Furinto (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2024)
In the context of a dynamic market like Indonesia, characterized by rapid population growth and increasing internet usage, OOH advertisers face unique opportunities. Indonesia is among the world's leaders in internet adoption, with a steady rise in users expected in the coming years. This digital transformation, led by social media platforms, offers advertisers a potent tool to connect with their audience. Social media, being a pivotal digital platform, has become integral to marketing strategies and customer engagement. Customers frequently turn to social media to inform their purchase decisions, which has propelled its significance in business strategies. Beyond facilitating customer-business interactions, it fosters customer-to-customer communication, transforming it into a multifaceted communication medium. PT. Saji Media Pratama, an out-of-home (OOH) advertising company based in Indonesia, has been operating since 1996 and has provided assistance to numerous companies in fulfilling their OOH requirements. However, in recent years, the company has encountered challenges as its digital marketing platform has struggled to attract new clients and has resulted in low brand awareness. This study examines the internal and external factors affecting the company in order to offer a digital marketing strategy aimed at increasing brand awareness and client acquisition. The company's internal analysis include the conduct of VRIO analysis, CRM analysis, and content analysis. The company's external analysis include the utilization of Porter's Five Forces analysis, customer analysis, and competitive analysis. The data was acquired by conducting a systematic review of relevant academic journals and by conducting in-depth interviews with both current employees of Saji Media and potential customers. The result will be developed using SWOT analysis to answer the research question and to propose a digital marketing strategy with RACE Planning Framework.